2022
DOI: 10.3389/fnut.2022.1046945
|View full text |Cite
|
Sign up to set email alerts
|

Investigating on the influence mechanism of sausage of sea bass on calcium absorption and transport based on Caco-2 cell monolayer model

Abstract: A monolayer Caco-2 cell model was established to explore the effects of sea bass sausage digestive juice containing phosphate on calcium ion transport. Differential proteins of Caco-2 cells treated with fish sausage juice were detected and analyzed by gene ontology (GO) functional annotation and kyoto encyclopedia of genes and genomes (KEGG) pathway analyses. Results revealed that after treatment with 0.23 mg/mL digestive juice of perch sausage in vitro, Caco-2 cell viability was the highest at 72 h (99.84%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Gel properties are important evaluation indexes of surimi products 5 . Adding appropriate exogenous substances is an effective means to improve the quality of freshwater fish surimi 6 . At present, exogenous additives that have been used in freshwater surimi include proteins, starch, hydrocolloids and other natural products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gel properties are important evaluation indexes of surimi products 5 . Adding appropriate exogenous substances is an effective means to improve the quality of freshwater fish surimi 6 . At present, exogenous additives that have been used in freshwater surimi include proteins, starch, hydrocolloids and other natural products.…”
Section: Introductionmentioning
confidence: 99%
“…5 Adding appropriate exogenous substances is an effective means to improve the quality of freshwater fish surimi. 6 At present, exogenous additives that have been used in freshwater surimi include proteins, starch, hydrocolloids and other natural products. Mi et al 7 found that the combined addition of soy protein isolate and transglutaminase (TGase) enhanced the waterholding capacity and gel properties of the straight-hole scallop adductor muscle.…”
Section: Introductionmentioning
confidence: 99%